An IRT Analysis of the Symptoms of Major Depressive Disorder. (June 2015) - Emmert-Aronson, Benjamin O.; Brown, Timothy A.
This study examines the psychometric properties of a major depressive episode using a large sample ( N = 2, 907) of outpatients with mood and anxiety disorders. A two-parameter logistic model yielded item threshold and discrimination parameters. A two-group confirmatory factor analysis was used to evaluate gender bias. Item thresholds fell along a continuum with the core features of depressed mood and anhedonia, along with fatigue, endorsed at lower levels of depression, and change in appetite and suicidal ideation endorsed at more severe levels. Item discriminations were highest for depressed mood and anhedonia, and lowest for change in appetite and suicidal ideation. The data indicate that the symptoms of depression assess a range of severity, with varying precision in discriminating depression. No gender differences were observed. Three exploratory symptom sets were compared with the full symptom set for depression, offering quantitative evidence that can be used to modify the psychiatric classification system.